2020
DOI: 10.1177/0309816820906354
|View full text |Cite
|
Sign up to set email alerts
|

Beyond mobilisation at McDonald’s: Towards networked organising

Abstract: This article uses McAlevey’s mobilising/organising dichotomy to analyse the recent McDonald’s mobilisation in Britain. It argues that this movement has had some impressive successes but building on these requires greater organising activities. However, conventional union organising techniques are unlikely to be successful in hospitality. Instead, the approach of another low-wage worker movement OUR Walmart demonstrates how social media can be used not only to benefit mobilising activities but to enable organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 13 publications
1
21
0
2
Order By: Relevance
“…In recent years, there has been a renewed interest in the extent to which the Internet and social media present opportunities for trade unions to broaden their membership base and improve levels of activism and mobilisation (Panagiotopoulos, 2012; Wood, 2020). These studies have been undertaken in the context of the established academic debate on ‘union revitalisation’, where unions adopt a range of strategies and tactics fundamentally aimed at growth (Ibsen & Tapia, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a renewed interest in the extent to which the Internet and social media present opportunities for trade unions to broaden their membership base and improve levels of activism and mobilisation (Panagiotopoulos, 2012; Wood, 2020). These studies have been undertaken in the context of the established academic debate on ‘union revitalisation’, where unions adopt a range of strategies and tactics fundamentally aimed at growth (Ibsen & Tapia, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this increased interest, there is still relatively little known as to how unions actually use social media platforms in terms of the content they post and extent to which the platforms are utilised to engage with other users. This is important as more unions are increasingly realising the potential of using such technologies to communicate with both existing and potential members (Simms et al, 2019; Upchurch & Grassman, 2016; Wood, 2020). This paper makes an important contribution to the growing literature in this area by providing the first systematic comparison of union use of social media, in terms of scope and content across two platforms, Facebook and Twitter, through a case study of the Public and Commercial Services union (PCS).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor has been the support of the Service Employees International Union, both in terms of human and financial resources and substantial contributions to the FF$15 debate on Twitter (Frangi et al, 2020). Wood (2020: 8) has urged caution, though, arguing that focusing on mobilising at the expense of organising is a shortcut to nowhere. Indeed, it is possible to do both: in a case study of three successive campaigns to unionize workers in Israel, Lazar (2020) found that activists achieved the mobilization of workers and recognition by management through leveraging the “portable‐visibility” afforded by social media networks (Facebook and WhatsApp) and mobile devices (smartphones) 8…”
Section: The Web 20 and 30 Eramentioning
confidence: 99%
“…Einige Zeit bestand die Hoffnung, dass die Machtasymmetrie zwischen globalen Unternehmen und ressourcenarmen Organisationen wie den Gewerkschaften im Netz aufgehoben wird, da mittels geringem Ressourceneinsatz Deutungen verbreitet und ein breiter Kreis an möglichen Protestteilnehmer*innen mobilisiert werden kann (Scott und Street 2001;Baringhorst 2009). Dieser Vorteil wird von den Ge-werkschaften allerdings relativiert, da die digitale Mobilisierung zumeist mehr Ressourcen bindet als es zunächst den Anschein hat (Baringhorst 2009;Wood 2020). Zudem wird das Machtungleichgewicht zwischen globalen Unternehmen und den Beschäftigten sowie ihren Vertreter*innen zum Teil auch im Netz reproduziert.…”
Section: Rahmenbedingungen Für Die Digitale Protestformierung Koordinierung Und Mobilisierung In Mnuunclassified
“…Im Fokus standen bislang die gewerkschaftliche Revitalisierung aufgrund sinkender Mitgliederzahlen durch die sozialen Medien (Dahlberg-Grunberg, Lunstrøm und Lindgren 2016;Lee 2010;Geelan 2013;Panagiotopoulos 2015;Lazar, Ribak und Davidson 2020) sowie die digitale Organisation von Gigworker*innen (Wood, Lehdonvirta und Graham 2018;Degner und Kocher 2018;Heiland und Schaupp 2020; Hoose und Haipeter in diesem Band). Alle bisherigen Studien rund um die Nutzung digitaler Medien während eines Arbeitskonfliktes haben zudem gemeinsam, dass sie sich primär auf die digitale Mobilisierung im nationalen Rahmen beziehen (Upchurch und Grassmann 2016;Pasquier und Wood 2018;Frangi, Zhang and Hebdon 2019;Ullah 2020;Wood 2020;Pasquier, Daudigeos und Barros 2020). Die Nutzung digitaler Medien in Arbeitskonflikten auf transnationaler Ebene fand dagegen bisher kaum Beachtung.…”
unclassified